Quantification of vitamin B12 in infant formula by dimensional liquid chromatography with solid phase extraction - CHU Xiaojun; TAO Baohua; LAI Shiyun; ZHANG jingshun; SONG Yiwen; REN Yiping (浙江大学学报. 农业与生命科学版, 2013)
Only a small amount of vitamin B12 is absorbed and utilized by human body. The suitable vitamin B12 levels can improve the utilization efficiency of folic acid. Excessive intake of vitamin B12 may cause allergic reactions, while vitamin B12 deficiency in infancy can lead to anemia. At present, most of the infants are not breastfeeding. Formula food supplemented with a suitable level of vitamin B12 is an important nutrient guarantee for healthy growth and development of infants. Thus, it is very necessary and important to develop a sensitive, efficient and accurate method for determination of vitamin B12. Currently, the commonly used methods for the determination of vitamin B12 in infant formula foods are microbial analysis methods. But they usually lead to get higher results than the real amounts because they do not distinguish vitamin B12 from its analogues. In addition, liquid chromatography technologies are also applied to analyze vitamin B12 in infant formulas. However, they have some disadvantages including long sample preparation time and high analysis costs.In the present study, a new method using solid phase extraction (SPE) coupled to two-dimensional liquid chromatography with ultraviolet detector was developed for the quantification of vitamin B12 in infant formulas. The different forms of vitamin B12 were transformed to cyanocobalamin by reacting with potassium cyanide solutions after the dissolved samples were digested with amylase. The extracts of samples were purified through the HLB SPE cartridges before they were injected into a dual gradient pump series liquid chromatography system in large volume injection. The samples were separated and enriched in ZORBAX GF-250 column (9.4 mm×250 mm, 4 μm) with the mobile phase of 7.5% acetonitrile in water. Afterwards they were switched into Agilent ZORBAX Bonus-RP column to analyze in gradient elution using 0.4% triethanolamine in water (pH=6) and 75% acetonitrile in water (including 0.4% triethanolamine, pH=6) as the mobile phases. The contents of vitamin B12 in samples were determined at the wavelength of 550 nm using external standard method.The developed method showed a good linearity (R2>0.999) when the calibration curve ranged from 2 to 40 ng/mL. The limit of detection and the limit of quantitation were evaluated as the signal-to-noise 3∶1 and 10∶1, and they were 1.0 and 2.5 μg/kg, respectively. The accuracy of the method was evaluated by employing the standard addition method. The spiked samples with 5.0, 10.0 and 50.0 μg/kg vitamin B12 standard (six portions for each spike level) were prepared and analyzed. The results showed that the spike recoveries were 88.0% - 94.8% with the relative standard deviation (RSD) of 2.54% -4.87% at the three spiked levels. The sample pretreatment of the established method involved enzymic hydrolysis using amylase, in order to maximize the extraction of vitamin B12. The transformation of vitamin B12 from different forms to cyanocobalamin with the best stability ensured the accuracy of quantitation. Most of the impurities were removed by employing HLB SPE cartridges during the clean-up of sample extracts. Compared with the purification technology using immunoaffinity cartridges, the experimental costs were significantly reduced and the time of sample preparation was shortened. After the sample extracts were further purified and enriched through the first dimensional liquid chromatography by large volume injection, they were analyzed at 550 nm by the dual column switching method. The wavelength of 550 nm minimized the signal interferences from impurities and further improved the accuracy of results.In conclusion, the two-dimensional liquid chromatography method with online column switching shows better sensitivity and reproducibility than the traditional liquid chromatography methods, and it is verified to be suitable for the determination of vitamin B12 in infant formulas.